2021
DOI: 10.3389/fmicb.2021.618999
|View full text |Cite
|
Sign up to set email alerts
|

Monthly Variation in the Macromolecular Composition of Phytoplankton Communities at Jang Bogo Station, Terra Nova Bay, Ross Sea

Abstract: Organic carbon fixed by photosynthesis of phytoplankton during the polar growing period could be important for their survival and consumers during the long polar night. Differences in biochemical traits of phytoplankton between ice-free and polar night periods were investigated in biweekly water samples obtained at the Korean “Jang Bogo Station” located in Terra Nova Bay, Antarctica. The average concentration of total Chl-a from phytoplankton dominated by micro-sized species from the entire sampling period was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 91 publications
(122 reference statements)
3
6
2
Order By: Relevance
“…In spring and summer, relatively large variations in temperature and salinity were observed with the melting of sea ice, but they were nearly stable during the winter period, as expected. The ice-free period in our study was only 12 days, which is a relatively shorter period compared with a previous study in which the ice-free period lasted more than a month [23].…”
Section: Environmental Conditionscontrasting
confidence: 66%
See 1 more Smart Citation
“…In spring and summer, relatively large variations in temperature and salinity were observed with the melting of sea ice, but they were nearly stable during the winter period, as expected. The ice-free period in our study was only 12 days, which is a relatively shorter period compared with a previous study in which the ice-free period lasted more than a month [23].…”
Section: Environmental Conditionscontrasting
confidence: 66%
“…Previous studies on the macromolecular composition of phytoplankton in the Ross Sea have been conducted primarily during spring and summer seasons [19][20][21][22]. Only a few studies [23] on the biochemical characteristics of phytoplankton have been previously conducted throughout a single year in the Southern Ocean. The Jang Bogo Station (JBS), located on the coast of Terra Nova Bay (TNB) in the Ross Sea, is one of the overwintering science stations in Antarctica.…”
Section: Introductionmentioning
confidence: 99%
“…Although Kim et al [29] reported the exceptionally high-calorie content in the productive polynyas of the Amundsen Sea, the calorie content from our study is in a similar range with the previous studies in the polar oceans (Table 7). According to Kim et al [32], the PRT concentration during the ice-free period in the Ross Sea of the Antarctic Ocean was 20 times increased than that during the ice-covered period, even though CHO or LIP concentrations showed a slight increase (Table 7). If it can be applied in the Arctic Ocean, the PRT concentration than other components might be largely increased under a decrease in sea ice conditions in the Arctic Ocean.…”
Section: The Implication Of Macromolecular Composition As Energy Content Aspectmentioning
confidence: 94%
“…Fabiano et al [41] reported the calorie content of 1.6 kcal m −3 in the Ross Sea of the Antarctic Ocean. Recently, Kim et al [32] observed the different calorie contents of phytoplankton between the two different periods in the Ross Sea of the Antarctic Ocean, indicating 1.3 kcal m −3 during the ice-free period and 0.6 kcal m −3 during the ice-covered season. Although Kim et al [29] reported the exceptionally high-calorie content in the productive polynyas of the Amundsen Sea, the calorie content from our study is in a similar range with the previous studies in the polar oceans (Table 7).…”
Section: The Implication Of Macromolecular Composition As Energy Content Aspectmentioning
confidence: 99%
See 1 more Smart Citation